Farinha de carcaça de Tilápia do Nilo (Oreochromis niloticus) em dietas para coelhos : desempenho, perfil lipídico, composição química e resistência ossea - Galan, Guilherme Legnani (2010)
The world aquaculture has grown over the years, and also the Brazilian aquaculture. The most cultivated species in Brazil is the Nile tilapia (Oreochormis niloticus). The Nile tilapia is widely used in the filleting process and this process results in a high quantity of waste as head viscera and carcass. The aim of this study was to create a fish meal from filleting wastes of fish (tilapia) and analyze its characteristics and its effect on the inclusion in rations of New Zealand White rabbits. The study was carried out at the Experimental Farm of Iguatemi (FEI) of Maringa State University of Maringá/PR. There were used 50 New Zealand White rabbits, , 35 days old. There were five treatments, T1 = 0%, T2 = 1%, T3= 2%, , T4 = 3% and T5 = 4% of inclusion of fish meal from waste filleting of Nile tilapia. The rabbits were randomly distributed in each treatment, with 10 replicates each one. The rabbits were weighed at the beginning of the experiment (35 days), after 50 days and at the end of the experiment (65 days old). After slaughter it was removed the right thigh of each animal for analysis of muscle (minerals composition, and lipids). The thigh bones were removed for testing the bone strength and chemical composition. The performance parameters blood lipid profile body composition bone composition and bone strength were analyzed using regression. For comparison of basal diet with each of the other diets it was used the Dunnett test (P <0.05). Experiment I, was calculated the weight daily gain and feed conversion and after slaughter the carcasses were weighed and calculated the gutted carcass yield. At slaughter blood was collected directly from the jugular vein for analysis of serum lipids. The results of the performance were the weight (2.277 kg 2.063 kg 2.103 kg 2.072 kg and 2.074 kg), daily weight gain (39.55 g, 36.53 g, 36.86 g, 37.46 g and 36.30 g ) feed conversion (3.83, 4.00, 4.04, 4.04 and 4.13) carcass weight (1.080 kg, 1.020 kg, 1.050 kg, 1.025 kg and 1.025 kg) and carcass ( 48.48%, 49.58%, 49.92%, 49.51% and 49.43%) respectively for the treatments 0%, 1%, 2%, 3% and 4% of inclusion of meal filleting waste of Nile tilapia. In the analysis of serum lipids were found the results of total cholesterol and HDL-C, LDL-C, VLDL-C and triglycerides and calcium and iron. Experiment II, was examined the quality characteristics of carcasses and bone strength. The quality characteristics of carcasses were moisture protein, fat, ash, calcium, phosphorus and iron. Another carcass quality feature was the fatty acid profile being estimated Σ SFA (saturated fatty acids), Σ MFA (monounsaturated fatty acid) and Σ PFA (polyunsaturated fatty acids). It was analyzed the chemical composition of bones and bone strength. There were no significant differences in the aminal's performance. The inclusion of waste meal of tilapia influenced the serum lipid HDL-c which had a significant difference showing a linear increase. For carcass quality there was no statistical difference in the amount of muscle protein, showing a quadratic effect on these values. The amount of lipids in muscle of rabbits fed with 3% addition of flour filleting waste of Nile tilapia was different from other treatments. There were differences in the amounts of calcium and phosphorus in the muscle of rabbits. The analysis of bone strength also showed no significant difference. Fishmeal from filleting waste of Nile Tilapia is an option for inclusion in the diets of farm animals. More research must be done with the use of meal in animal production, especially in relation to other species of animals, considering the level of inclusion and treatment time.